Changes in abiotic influences on seed plants and ferns during 18 years of primary succession on Puerto Rican landslides. (3rd April 2013) - Walker, Lawrence R.; Shiels, Aaron B.; Bellingham, Peter J.; Sparrow, Ashley D.; Fetcher, Ned; Landau, Fred H.; Lodge, Deborah J.; Kitzberger, Thomas
Summary Abiotic variables are critical drivers of succession in most primary seres, but how their influence on biota changes over time is rarely examined. Landslides provide good model systems for examining abiotic influences because they are spatially and temporally heterogeneous habitats with distinct abiotic and biotic gradients and post‐landslide erosion. In an 18‐year study on 6 Puerto Rican landslides, we used structural equation models to interpret the changing effects of abiotic influences (landslide dimensions, slope, aspect, elevation, parent material and related soil properties) on seed plants (density and diversity), tree fern density, scrambling fern cover, canopy openness and soil development (nitrogen, soil organic matter, pH and cation exchange capacity). Seven years after landslide formation, catchment size (the landslide area above the point of measurement) was the key abiotic factor influencing plants. The larger the catchment the greater was the diversity and density of seed plants. Conversely, the smaller the catchment the greater was the density of tree ferns and the cover of scrambling ferns. Eighteen years after landslide formation, landslide slope was the key abiotic influence. The greater the slope, the lower was the density and diversity of seed plants and the greater was the scrambling fern cover. Aspect, particularly east‐facing slopes exposed to wind disturbances, positively influenced tree fern densities at both 7 and 18 years and negatively influenced seed plants and scrambling ferns at 18 years. Soils were least developed, that is, had lowest soil nitrogen and organic matter concentrations, after 18 years on steep slopes (like seed plants); soils were most developed near landslide edges, on hurricane‐exposed slopes (like tree ferns) and where there were high soil potassium concentrations. Synthesis. Abiotic variables have important influences on plant succession on landslides and the relative influence of different abiotic variables changes with time. Improved predictability of temporal dynamics will rely not only on understanding the effects of initial disturbances and subsequent biological responses but also on the different and changing influences exerted by each abiotic variable.